Mister Miracle : the great escape - Johnson, Varian (DC Comics, 2022)
Scott Free, a student at the Goodness Academy on the planet Apokolips, wants to escape to Earth but falls in love with the head of the Female Furies--the one person tasked with ensuring he never escapes.